2022 17th International Conference on Control, Automation, Robotics and Vision (ICARCV) 2022
DOI: 10.1109/icarcv57592.2022.10004249
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Virtual Testing of Autonomous Vehicles

Abstract: The worldwide development of Autonomous Vehicles (AVs) has also encouraged the use of software simulators for virtual testing of AVs. However, the effectiveness of the AV simulators is constrained by numerous challenges, such as their computational cost and lack of fidelity in specific areas. In this paper, we describe the modality of virtual testing and its benefits for AV development and validation. Moreover, we summarize and provide an overview of the state-of-the-art AV simulators, their limitations, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The testing and evaluation of automated vehicles can be performed on real roads or in virtual environments [38]. Considering that several millions of test kilometers must be completed to effectively test and evaluate automated vehicles [39], it can be concluded that the real testing and evaluation of automated vehicles are limited by factors such as cost, time, and scalability [40]. Thereby, the virtual environment was first adopted to test and evaluate automated vehicles in this paper to verify the effectiveness of the proposed method.…”
Section: Examples Of the Subjective And Objective Evaluation Of Autom...mentioning
confidence: 99%
“…The testing and evaluation of automated vehicles can be performed on real roads or in virtual environments [38]. Considering that several millions of test kilometers must be completed to effectively test and evaluate automated vehicles [39], it can be concluded that the real testing and evaluation of automated vehicles are limited by factors such as cost, time, and scalability [40]. Thereby, the virtual environment was first adopted to test and evaluate automated vehicles in this paper to verify the effectiveness of the proposed method.…”
Section: Examples Of the Subjective And Objective Evaluation Of Autom...mentioning
confidence: 99%